Natural orifice translumenal endoscopic radical prostatectomy - Mitchell R. Humphreys (Therapeutic Advances in Urology, 2012)
The purpose of this publication is to document the evolution of a new surgical procedure for the treatment of carefully selected patients with organ confined localized prostate cancer. Natural orifice surgery represents a paradigm shift in the surgical approach to disease, although its adoption into clinical practice has been limited to date. This manuscript describes the development of natural orifice translumenal endoscopic surgical radical prostatectomy (NOTES RP). The laboratory, animal, preclinical and early clinical experiences are described and detailed. While the early experiences with this approach are promising and encouraging, more information is required. Despite the early successes with the procedure, long-term oncological and functional outcomes are essential and more work needs to be done to facilitate the teaching and ease of the NOTES RP.